Remark on optimal investment in a market with memory - Inoue, A.; Nakano, Y. (Інститут математики НАН України, 2007)
We consider a financial market model driven by a Gaussian semimartingale with stationary increments. This driving noise process
consists of n independent components and each component has memory described by two parameters. We extend results of the authors
on optimal investment in this market.